The Role of Women Farmers In Decision Making In Lowland Rice Farming (Oryza Sativa L) (Case Study Of Waitonipa Village, Northeast Seram District) - Helmy D. Suciati; Aphrodite M. Sahusilawane; Noviar F. Wenno (International Journal of Economics, Business and Innovation Research, 2023)
This study aims to find and analyze the factors that cause the low role of women farmers in decision making in paddy rice farming. The data analysis method used is multiple linear regression analysis. The results of data analysis show that the factors that significantly influence the low role of women farmers in decision making in lowland rice farming are age, experience, land ownership, land area and motivation to meet needs. While factors such as education, number of family dependents and income do not significantly affect the low role of women farmers in decision making in paddy rice farming.